MAPPING POWER AND SPACE IN DETECTIVE FICTION: FROM CHRISTIE’S CLOSED CIRCLES TO CHANDLER’S URBAN LABYRINTHS - Spataru, Elena Spataru (Universitas Islam Malang, 2025)
This article examines the complex interplay between spatial representation, power dynamics, and ideology in crime fiction, specifically comparing Agatha Christie’s Golden Age detective stories with Raymond Chandler’s hardboiled urban novels. Utilizing theoretical frameworks established by Michel Foucault, Henri Lefebvre, and other spatial theorists, it investigates how space in these works functions as a dynamic agent rather than a mere passive backdrop. In Christie’s books, the enclosed settings of country estates and English villages—characterized by moral scrutiny and social hierarchy—serve as ideological microcosms where crime, investigation, and societal restoration occur inside regulated confines. In contrast, Chandler's Los Angeles exemplifies spatial disorder: a disjointed, ethically ambiguous maze where knowledge and understanding falter beneath the burden of modernity. The study contends that both authors convert narrative space into a tool for social critique, expressing cultural worries over order, authority, and knowledge through meticulous textual and theoretical analysis. The paper posits that detective fiction transcends a simple puzzle genre, functioning as a cartography of contemporary consciousness that delineates the conflicts between containment and disorder, visibility and secrecy, conservatism and revolt.